The lyricism of Horace : analyses of five of the odes I-III as lyric poems in the light of the classical and modern conceptions of the lyric poem - Henderson, W. J.,1937- (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.A.) -- University of Stellenbosch, 1964.